Pilgrimage as a form of transcendental communication: A study at the burial site of Habib Abdurrahman bin Abdullah Al-Habsyi - Achmad Jamil; Rizki Briandana; Ahmad Hannan; Muhammad Raqib Mohd Sofian (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
Transcendental communication is a part of ritual communication. This form of communication is the least discussed in the discipline of communication. This study discusses transcendental communication in a pilgrimage to the burial site of Habib Abdurrahman in Cikini, Jakarta. The paradigm of this study is a constructivist paradigm using a qualitative approach with a case study method. The techniques used for data collection are interviews, observation, literature study, and documentation. The results show that the meaning of pilgrimage as a medium for transcendental communication is built on three things, namely, communicative situations, communicative events, and communicative acts, all of which can be observed from the attitudes of the pilgrims. These three elements are based on spiritual values in Islamic religious beliefs strengthened by the Sunnah of the Prophet Muhammad and continued by generations after that until today. Thus, this study contributes to the existence of Islamic communication scholarship where every communication behavior in everyday life is always based on human personal communication with the creator.***Salah satu bentuk komunikasi ritual adalah komunikasi transendental. Bentuk komunikasi transendental ini paling sedikit dibicarakan dalam disiplin ilmu komunikasi. Studi ini bertujuan membahas komunikasi transendental dalam ziarah ke makam Habib Abdurrahman di Cikini, Jakarta. Paradigma pada penelitian ini adalah paradigma konstruktivis dengan menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, studi kepustakaan dan dokumentasi. Hasil penelitian menunjukkan makna ziarah sebagai media komunikasi transendental dibangun pada 3 hal yaitu, situasi komunikatif, peristiwa komunikatif, dan tindak komunikatif, yang ketiganya dapat diamati dari sikap para peziarah. Ketiga elemen itu didasari atas nilai-nilai spiritual dalam keyakinan agama Islam yang dikuatkan oleh Sunnah Nabi Muhammad dan dilanjutkan oleh generasi-generasi setelahnya sehingga saat ini. Dengan demikian, studi ini berkontribusi bagi eksistensi keilmuan komunikasi Islam dimana setiap perilaku komunikasi berbasis pada komunikasi personal manusia dengan sang pencipta.